MOLECULAR AND SEROLOGICAL IDENTIFICATION OF FOOT-AND-MOUTH DISEASE VIRUS SEROTYPES IN CATTLE OF BASRAH PROVINCE - Zainab M. Salem; Adnan M. Al-Rodhan (Basrah Journal of Veterinary Research)
This study was conducted on serum from 6 different regions covering all parts of the Basrah province during the period from October 2012 to June 2013 in order to determine the prevalence of foot and mouth disease in bovine species. From the serology results, the overall prevalence of this disease was(72.7%.) . Of the 165 samples subjected to Nonstructural protein (NSP) enzyme linked immunosorbent assay (ELISA) screening test, 120 were interpreted as positive representing (72.7%.) while the other 45 samples were negative representing 27.3%. The seropositivity significantly associated with age groups (p0.05) while the difference among age groups was significant (P < 0.05)